Inhibition of H3K27me3 Histone Demethylase Activity Prevents the Proliferative Regeneration of Zebrafish Lateral Line Neuromasts - Bao, Beier; He, Yingzi; Tang, Dongmei; Li, Wenyan; Li, Huawei (Frontiers in Molecular Neuroscience, 2017)
The H3K27 demethylases are involved in a variety of biological processes, including cell differentiation, proliferation, and cell death by regulating transcriptional activity. However, the function of H3K27 demethylation in the field of hearing research is poorly understood. Here, we investigated the role of H3K27me3 histone demethylase activity in hair cell regeneration using an in vivo animal model. Our data showed that pharmacologic inhibition of H3K27 demethylase activity with the specific small-molecule inhibitor GSK-J4 decreased the number of regenerated hair cells in response to neomycin damage. Furthermore, inhibition of H3K27me3 histone demethylase activity dramatically suppressed cell proliferation and activated caspase-3 levels in the regenerating neuromasts of the zebrafish lateral line. GSK-J4 administration also increased the expression of p21 and p27 in neuromast cells and inhibited the ERK signaling pathway. Collectively, our findings indicate that H3K27me3 demethylation is a key epigenetic regulator in the process of hair cell regeneration in zebrafish and suggest that H3K27me3 histone demethylase activity might be a novel therapeutic target for the treatment of hearing loss.